ANALISIS PORTOFOLIO OPTIMAL MENGGUNAKAN MULTI INDEX MODEL (Studi Kasus: Kelompok Saham IDX30 periode Januari 2014 – Desember 2018) - Bramadita Kunni Fauziyyah; Alan Prahutama; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2019)
Investment is the placement of a number of funds at this time in the hope of making a profit in the future. The purpose of investors investing is to get many profit by understanding that there is a possibility of losses. But, the higher the expected return then the risk also greater. The method to minimize risk is portfolio. One of the optimum portfolio method is Multi Index Model. Multi Index Model is model that use more than one index or factor that affects the return on stock. The stock in this research is 10 stocks of IDX30 period January 2014 – December 2018. Index in this research is IHSG, Hang Seng Index and DJIA. Multi Index Model has assumptions: residual variance of stock i equals , variance of index j equals , E(ci) = 0, covariance between index equals 0, covariance between the residual for stock and index equals 0 and covariance between the residual for stock equals 0. The result of this research is there are 4 stocks that fulfill the assumpions to be made as the optimum portfolio, that is GGRM (Gudang Garam Tbk) 23.67%, UNVR (Unilever Indonesia Tbk) 37.09%, BBCA (Bank Central Asia Tbk) 25.15% dan ASII (Astra International Tbk) 14.09% with a value of expected return portfolio is 1.19% and risk of portfolio is 3.79%. Keywords: Investment, Optimum Portfolio, Multi Index Model